Percolation Threshold Enables Optical Resistive‐Memory Switching and Light‐Tuneable Synaptic Learning in Segregated Nanocomposites. (28th May 2019) - Jaafar, Ayoub H.; O'Neill, Mary; Kelly, Stephen M.; Verrelli, Emanuele; Kemp, Neil T.
Abstract: An optical memristor where the electrical resistance memory depends on the history of both the current flowing through the device and the irradiance of incident light onto it is demonstrated. It is based on a nanocomposite consisting of functionalized gold nanoparticles in an optically active azobenzene polymer matrix. The composite has an extremely low percolation threshold of 0.04% by volume for conductivity because of the aggregation of the conducting nanoparticles into filamentary nanochannels. Optical irradiation results in photomechanical switching through expansion of the thin film from above to below the percolation threshold, giving a large LOW/HIGH resistance ratio of 10 3 . The device acts as an artificial synapse, the conductivity or plasticity of which can be independently modulated, either electrically or optically, to enable tunable and reconfigurable synaptic circuits for brain‐inspired artificial intelligent or visual memory arrays. The lifetime of the resistive‐memory states is also optically controllable, which enables spatial modulation of long‐ and short‐term memory. Abstract : The resistance ratio between the memory states of an optical memristor is photomechanically tunable; photoexpansion breaks conducting nanochannels of gold nanoparticles doped in an azobenzene polymer, shifting the conductivity (σ) from above to below the percolation threshold. The optically controllable lifetime of such resistive‐memory states enables spatial modulation of long‐ and short‐term memory in an artificial synapse.